An examination of B2O3 in magnesium oxide obtained from seawater - Martinac, Vanja (Materiali in tehnologije, 2001)
The study has been examining the possibility of a repeated application of the agent used to rinse the precipitate of magnesium hydroxide obtained from seawater by substoichiometric precipitation with the addition of 80% of the stoichiometric quantity of dolomite lime as the precipitation agent. The purpose of the study has been to ensure a high-purity product i.e. magnesium oxide, particularly regarding the B$_{2}$O$_{3}$ content, because the hot-strength properties of certain magnesia refractory products are significantly affected by their boron content. The rinsing agent was alkalized distilled water with a pH=12.5, which was alkalized by the addition of concentrated NaOH prior to each use. The aim of the study was to reduce the amount of magnesium hzdroxide rinsing agent, while retaining satisfactory level of purity for the magnesium oxide product. The product quality was established by determining the concentrations of MgO, CaO and B$_{2}$O$_{3}$ in the calcined magnesium oxide. Examinations were carried out with magnesium oxide samples prepared by rinsing the precipitate with: fresh alkalized distilled water, recycled alkalized distilled water, non-alkalized distilled water and without previous rinsing of the magnesium hydroxide precipitate. The results indicate that by using the recycled alkalized distilled water with a pH=12.5, the B$_{2}$O$_{3}$ content in the MgO samples (80% precipitation) amounts to 0.0807 mass %, which is 58% less than the B$_{2}$O$_{3}$ content in samples prepared without rinsing of the magnesium hzdroxide precipitate (B$_{2}$O$_{3}$ = 0.1937 mass %).
Keywords: usedanje; kovinski oksidi; borov oksid; magnezijev oksid; morska voda; izpiranje